THE CHARACTERISTIC OF SYAR’IYAH COURT DECISION INTO UNITARY STATE OF THE REPUBLIC OF INDONESIA ( SYAR’IYAH COURT REGIONAL CASES OF NANGGROE ACEH DARUSSALAM PROVINCE) - Delfina Gusman (Faculty of Law, Universitas Riau, 2023)
The Sharia Court is a judicial institution within the scope of the Unitary State of the Republic of Indonesia which has important position in the Indonesian judicial system. The authority of the Syar'iyah Court is regulated through the Qanun of the Province of Nanggroe Aceh Darussalam (Article 1 point 15 of Law Number 11 of 2006 concerning the Government of Aceh). The limitations of the qanun that regulate the authority of the Sharia Court raises its own problems for judges to decide cases. Therefore, it is necessary to formulate and identify the characteristics of the decisions of the Sharia Court in the Province of Nanggroe Aceh Darussalam. This research is a normative legal research with a descriptive-analytic. The results show that the characteristics of the decisions of the Syar'iyah Court in the Unitary State of the Republic of Indonesia are in the form of the decisions of the Syar'iyah courts, the types of cases that are decided at the Syar'iyah courts, and on the basis of legal considerations in the decisions of the Sharia Courts. The characteristics of the decisions of the Sharia Court in these three aspects are not found in other court decisions in the Unitary State of the Republic of Indonesia. Jinayat cases are characteristic of the types of cases that are decided at the Sharia court. This type of Jinayat case shows the development of the concept of the Unitary State in the implementation of regional autonomy. The basis for legal considerations in the decision of the Sharia Court are facts (events and law), trial facts, sources of law and statutory regulations.